Patterns of distant organ metastases in esophageal cancer: a population-based study - Ai, Dashan; Zhu, Hanting; Ren, Wenjia; Chen, Yun; Liu, Qi; Deng, Jiaying; Ye, Jinjun; Fan, Jianhong; Zhao, Kuaile (Journal of Thoracic Disease; Vol 9, No 9 (September 27, 2017): Journal of Thoracic Disease, 2017)
Background: Esophageal cancer is the eighth most common cancer worldwide. The prognosis of esophageal cancer patients is dismal, especially those with distant organ metastasis. However, there are few studies describing the patterns of distant metastasis in esophageal cancer systematically. Methods: We gathered the data from Surveillance Epidemiology and End Results (SEER) database between 2010 and 2013. Categorical variables were analyzed by the Pearson Chi square test, and continuous variables were analyzed by the two-sample t test. Survival estimation and comparison among different variables were performed using Kaplan-Meier method. A multivariable logistic regression model was used to calculate odds ratios (OR) for sex, age, anatomical site, and histological type on specific metastases. Proportional hazards regression model was conducted to obtain adjusted hazard ratio (HRs) for different predictors of overall survival. Results: A total of 9,934 patients were eligible. Liver was the most common metastatic site in the patients of esophageal cancer and followed by lung, bone and brain. Some clinical features, including age, sex, histology type and histologic grade were independent risk factors for different sites of metastasis. Younger age, poorer differentiation, adenoma type and more metastatic sites might lead to poorer prognosis. Conclusions: Our findings revealed the patterns of metastasis in esophageal cancer, which could help clinicians to identify patients with metastasis and provide proper treatment.